PENDAMPINGAN PRAKTEK PEMBUATAN PUPUK KOMPOS OLAHAN SAMPAH RUMAH TANGGA - Diah Isnaini Asiati; Nina Sabrina; Choiriyah (Studi Kasus Inovasi Ekonomi, 2021)
Without a proper management, the surrounding waste will cause a lot of problems. There are several methods of waste disposal that can be chosen. Beside making clean environment, waste disposal can be an enjoyable joint activity as well as a form of household responsibility for daily consumption activities. Following this, waste disposal activities have been a choice by women who are members of Aisyah Ranting Talang Kelapa’s group. At first, a brief explanation about compost making process from household kitchen waste as the raw material was given to them. Afterwards, it was continued by the practice of compost making from the beginning to the end of result. During that time, the mothers seemed to show their enthusiasm in participating the activities by being directly involved in the making process of chili fertilizer while questioning for better understanding at the same time. Thus, these activities were expected to be carried out in their houses and also opened for any long-term possibilities that it will be developed into a profitable business charity.. Keywords: Compost; household kitchen waste; profitable